2019
DOI: 10.1002/mawe.201800229
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amorphous silica by rice husk ash on physical properties and microstructures of recycled aluminium chip AA7075

Abstract: High strength to weight ratio of aluminium reinforced as metal matrix composites is a well known material used in automotive application. The effects of recycled aluminium chips AA7075 with amorphous silica by rice husk ash on the physical properties and microstructure were investigated. Recycled aluminium chip AA7075 was reinforced with agro waste of amorphous silica rice husk ash i. e., 2.5 %, 5 %, 7.5 %, 10 % and 12.5 %. Samples of these metal matrix composites were prepared by cold compaction method due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…The following is the chemical composition of rice husk ash obtained from some representative literatures. [26][27][28][29][30][31][32][33][34][35][36]…”
Section: Chemical Properties Of Rice Husk Ashmentioning
confidence: 99%
“…The following is the chemical composition of rice husk ash obtained from some representative literatures. [26][27][28][29][30][31][32][33][34][35][36]…”
Section: Chemical Properties Of Rice Husk Ashmentioning
confidence: 99%
“…Then, ultrasonic bath apparatus, FRITSCH -ultrasonic cleaner Labarette 17 was used to clean the milled Aluminium chip with duration of 1 hour using an acetone solution to remove oil, grease and any impurities. Lastly, the milled Aluminium chip is drying using drying oven at 75°C temperature in 1 hour to remove the remaining acetone solution from the Aluminium chip [12][13][14][15][16].…”
Section: Preparation Of Chips Aa7075mentioning
confidence: 99%
“…These novel materials offer great opportunities for advanced material and development. Depending on the application, the characteristics of the metal matrix can be customized to the material [16,17]. Nowadays, many studies on recycled wastes material have been reported owing to the varied application of metal matrix composite.…”
Section: Introductionmentioning
confidence: 99%